Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1186/1471-2415-14-105
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of macular thickness changes in Leber’s hereditary optic neuropathy by optical coherence tomography

Abstract: BackgroundTo characterize macular thickness (MT) changes in Leber’s hereditary optic neuropathy (LHON) patients by cirrus HD-optical coherence tomography (OCT), and to study the correlation between MT and best corrected visual acuity (BCVA).MethodsFifty-two eyes from 52 consecutive LHON patients and 14 eyes from 14 age- and sex-matched healthy controls were scanned by OCT. Affected eyes were classified into five groups according to disease duration (1st group: ≤3 months; 2nd group: 3–6 months; 3rd group: 6–9 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 12 publications
4
14
0
Order By: Relevance
“…Central field defects and blind spot enlargement were common findings, in keeping with previous investigations [18]. e current study showed that that the thickness of the RNFL around the optic disc and surrounding the macula did not reduce in the acute stage but reduced significantly in the chronic stage of the disease, corroborating previous reports [19,20]. e pattern ERG N95 and approximately 70% of P50 originate in the retinal ganglion cells.…”
Section: Discussionsupporting
confidence: 92%
“…Central field defects and blind spot enlargement were common findings, in keeping with previous investigations [18]. e current study showed that that the thickness of the RNFL around the optic disc and surrounding the macula did not reduce in the acute stage but reduced significantly in the chronic stage of the disease, corroborating previous reports [19,20]. e pattern ERG N95 and approximately 70% of P50 originate in the retinal ganglion cells.…”
Section: Discussionsupporting
confidence: 92%
“…This result confirms a recent study23 evaluating total macular thickness in patients with LHON, stratified in five subgroups based on disease duration. The authors separately analysed the inner and the outer ring in nine different sectors with methodology corresponding to the Early Treatment Diabetic Retinopathy Study.…”
Section: Discussionsupporting
confidence: 91%
“…As it has been previously reported, the temporal fibres of the peripapillary retinal nerve fibre layer were the most severely affected in our patient, with relative sparing of the nasal ones . Recent publications have reported changes in the macular ganglion cell layer in patients with LHON during the initial days of visual loss, and have suggested these changes may precede the conversion from carrier to disease status …”
Section: Discussionsupporting
confidence: 81%